The inverted classroom in education: A resilient methodological tool for social change - Erazo Rodríguez, Miriam Elizabeth; Viñan Carrasco, Luis Miguel; Murillo Naranjo, Myriam Elizabeth; Rodríguez Galán, Andrés Leandro (Technium Social Sciences Journal, 2020)
The implementation of innovative experiences within the educational context is part of a transformation process where new information and communication technologies (hereafter, ICT) promote the use of methodological tools that contribute to conventional classroom systems, through the creation of virtual training environments that establish the development of audiovisual language and facilitate communication. The objective of the following article is to reflect on the implementation of the inverted classroom as a learning tool for social change that breaks the traditional paradigms of education and represents an option for redesign the curriculum model. It is also part of the Education Research project and Literacy in Communication and Audiovisual and Interactive Arts applied in intercultural contexts for the conservation and diffusion of cultures and ancestral knowledge in conflict or isolation. The study presents a qualitative-quantitative and documentary methodology, and a case of study uses a bibliographic investigation that contrasts the information with the data obtained from the application of data collection instruments such as surveys, and observation; that will allow establishing the appropriate parameters, and discussing the results that show the importance of the use of the inverted classroom in the teaching-learning processes to strengthen resilient, autonomous and meaningful learning, recognizing students as the main protagonists of new knowledge.